Os sentidos do ensino de Ciências nos anos iniciais do Ensino Fundamental: o lugar da professora formada em Pedagogia - Wendling, Cléria Maria (2022)
The process of professional development of teachers occurs through progress in professional life as well as through the development of the profession itself. Thus, investigating the meanings of the professional development of teachers who work in the early years of elementary school requires revealing the processes of constitution of the profession itself, as well as the individual achievements achieved over time by these professionals. This thesis sought to answer the following research question: What meanings about the teaching of Science are produced in the professionalization processes of teachers in the early years of Elementary School? In order to know the professional development of teachers who work in Science teaching in the early years of elementary school, we developed this qualitative research with documentary research and interviews that were analyzed with discursive textual analysis. The document analysis used several official documents and the scientific production from 2009 to 2018 developed by masters and doctorates from dealing with science teaching at that level of education. We conducted interviews with 5 teachers at the beginning of their careers and 5 experienced teachers to find out about the different training demands of these two distinct phases of professional development. The discursive textual analysis revealed the institutional professionalization processes for acting in the early years of Elementary School, the historical reconstruction of the institutionalization of the teaching profession, the definition of the training necessary for professional performance, the production of academic knowledge about the profession and the representations of teachers about the profession and the meanings of science teaching.